Knowledge and Practices of Self-Care among People with Diabetes in South Western Uganda: A Cross-Sectional Study at a Regional Referral Hospital in Mbarara City.: Diabetes self-care knowledge and practice in Mbarara city. - Nakidde, Gladys; Kamoga, Ronald; Katushabe, Eve; Luwaga, Rachel; Mwanja, Mercy. M (Student's Journal of Health Research Africa, 2022)
Background: Diabetes is a chronic metabolic disease with increasing prevalence globally. Glycemic control is the ultimate management goal possible through self-care activities predominantly patient-driven and enhanced by one’s knowledge. These consequently minimize associated adverse complications hence maintaining the quality of life among people with diabetes. Self-care knowledge and practice are globally found unsatisfying to control glycemia among many diabetic populations. There is a critical need to assess current knowledge and practice regarding self-care among diabetic people to control their diabetes. Methods: We conducted a hospital-based cross-sectional study on 228 participants who were living with diabetes for at least six months since diagnosis. A standard tool, adopted and modified to suit the setting was used; the self-report Diabetic Knowledge Test Questionnaire for self-care knowledge and a revised version of the Summary Diabetes Self-Care Activities Questionnaire for practice. Both descriptive and logistic analysis was done using Stata software, version 13. Results: Adequate diabetes self-care knowledge was average (56%) and adequate self-care practice was below average (35%). Major gaps in foot care, blood glucose testing, hypoglycemia recognition, and management. Multiple logistic regression revealed longer duration with diabetes and more frequency of receiving health education highly associated with adequate self-care knowledge and practice (duration ≥ 11 years, AOR: 2.9; P=0.014) and health education on every clinic visit (AOR: 4.0; P=0.005) for self-care knowledge while duration ≥ 6 years (AOR=3.3, P-value = 0.011) and health education twice from the time they started clinic visits (AOR= 0.2, P= 0.048) for self-care practice. Conclusion: Interventions should be developed focusing on precise and user-friendly health education packages translated to local languages, and eye-catching to the audience, priority to newly diagnosed and less educated. A further study assessing appropriate health education delivery avenues to clients of various characteristics, especially rural communities.